University Business Incubators: An Institutional Demand Side Perspective on Value Adding Features - Sven Dahms; Suthikorn Kingkaew (Entrepreneurial Business and Economics Review, 2016)
Objective: The purpose of this article is to investigate differing demands for university business incubator’s value adding features. It introduces an institution based perspective to guide the argumentation. A framework has been developed, which is grounded in recent entrepreneurship theory and studies related to business incubator development. Research Design & Methods: An exploratory empirical study has been conducted to test the framework using participants from the United Arab Emirates and Thailand. The survey questionnaire was developed and tested before applying to the empirical study. Findings: The findings indicate variation in demands for incubator features in particular related to infrastructure and networking services. In line with the expectations, no differences have been found for the business support services. We also found that a more general strategy and goals seem to be preferred over a more narrow industry focus. Implications & Recommendations: The framework and our empirical findings suggest that university business incubators should take into consideration institutional differences between the countries in order to increase acceptance of the incubator concept,especially in developing countries. Contribution & Value Added: The study addresses a research gap, identifying crosscountry differences in the demand of potential entrepreneurs for value adding features provided in University Business Incubators (UBI).